PREDIKSI LIVABILITY KOTA SURABAYA BERDASARKAN KEPADATAN POPULASI MENGGUNAKAN MODEL LOGISTIK DAN HIRARKI KLASTER - Triska Ilma Wardani; Shoffan Shoffa; Wahyuni Suryaningtyas (MUST: Journal of Mathematics Education, Science and Technology, 2025)
This study aims to predict the population of Surabaya City in 2035 using the logistic model and to classify the livability level of each district based on population density. Secondary data were obtained from Badan Pusat Statistik (BPS) for the years 2010–2023. The population projection was conducted using logistic differential equations, while classification was carried out through agglomerative hierarchical clustering analysis using SPSS. The results indicate that districts with high population density, such as Sawahan, Bubutan, and Simokerto, fall into the low livability category. In contrast, districts like Rungkut, Sambikerep, and Gunung Anyar are categorized as highly livable due to their lower density. These findings suggest an inverse relationship between demographic pressure and livability. The classification output, visualized through maps, provides spatial insight to support urban spatial planning and policy-making. The study recommends equitable infrastructure development, population growth control, and service improvement in less livable areas to enhance the overall quality of life in Surabaya.